Analisis interval waktu perawatan preventif pada Paper Machine dengan metode reliability centered maintenance (RCM) - -, Erwin -; Zebua , Eduarman; Njoman Manik , Ni (Universitas Muhammadiyah Metro, 2024)
The maintenance process and preventive measures on paper machines need to be studied further, this will affect the production process and paper machine performance. This study aims to determine the criticality of the drying machine failure and determine the preventive measures that must be taken in the maintenance of the dryer and determine the time interval for the maintenance of the dryer machine components. To overcome this problem, this research was made using the Reliability Centered Maintenance (RCM) method. RCM can be interpreted as a process used in determining what to do for the machine, wherein in the RCM methodology there is one FMEA calculation in dealing with critical components in the dryer. Based on data processing and analysis using the RCM method, the maintenance time interval results from the maintenance of the dryer component. The results found are drums/cylinders with maintenance intervals of 82.7 hours, components of all pipes with maintenance intervals of 91.1 hours, and gear components with maintenance intervals of 110.7 hours. The implications for the company's factory regarding preventive maintenance intervals will have an impact on improving the production process and performance of paper machines through early prevention of machine failures that often occur.